Ameryka widziana oczyma Czesława Miłosza - Geambaşu, Constantin (Postscriptum Polonistyczne, 2020)
The article discusses several “curiosities of American spirit” on the basis of the volume of essays A View of San Francisco Bay: the duality of Americans (based on hesitation between success and despair), nihilism noticed especially among the representatives of the younger generation, arrangement of spatial hierarchy, tearing America into two hostile camps (pure, noble minds and simple people’s minds), arrogance of one’s own “I” (being the fundamental cause of great achievements in technology and science), dissonance between biblical spirit and technological progress etc. Besides their cognitive value, Miłosz’s essays are also a great lesson of imagology on America perceived by the comparatist’s eyes.